A Room for “Adam and Steve” at Mrs. Murphy’s Bed and Breakfast: Avoiding the Sin of Inhospitality in Places of Public Accommodation - Forman, David M. (Columbia Journal of Gender and Law, 2012)
This article aims to encourage a vital and evolutionary step forward in understanding how multifaceted legal processes shape, and should shape, thinking about gay and lesbian couples within religious communities and the body politic. The article begins by providing context that illustrates the place-based and diffuse nature of an ongoing culture war between civil rights and religious freedom, further exposing the painful irony inherent in using misinterpretations of the Sodom and Gomorrah parable to reinforce inhospitality. The article describes a state-by-state patchwork of nondiscrimination laws governing places of public accommodation and explores the Jim Crow origins of the “Mrs. Murphy” exception that has been incorporated into a handful of state nondiscrimination laws. The article then examines how existing legal frameworks address claims of sexual orientation discrimination alongside defenses based upon religious freedom. Finally, this article seeks to accelerate an emerging trend toward including sexual orientation as a protected category in our nation’s nondiscrimination laws, by highlighting an opportunity to counter religious misinterpretations currently reflected in the prevailing cultural narrative.